2014
DOI: 10.1186/s40529-014-0052-8
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Begonia sect. Coelocentrum, B. guixiensis and B. longa, from Sino-Vietnamese limestone karsts

Abstract: BackgroundIn our recent molecular phylogenetic study of Asian Begonia, two undescribed species, B. guixiensis sp. ined. (S. Guangxi, China) and B. longa sp. ined. (Vietnam), were sampled and placed within the strongly supported clade composed of Begonia sect. Coelocentrum and other co-distributed rhizomatous species in the Sino-Vietnamese limestone karsts. While Begonia sect. Coelocentrum has been recircumscribed based on the phylogenetic relationships, B. guixiensis sp. ined. and B. longa sp. ined. remain ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…4F). Chromosome cytology:-The Asian section Coelocentrum consistently shows the chromosome number of 2n = 30 (Peng et al 2012(Peng et al , 2013(Peng et al , 2014a, with the exception of some probable intraspecific autotriploid individuals with 2n = 45 in B. longgangensis C.- I Peng & Yan Liu (2013: 54-44: 2) (Peng et al 2013). In this study, the diploid count of 2n = 30 was documented for Begonia calciphila (Fig.…”
Section: Introductionsupporting
confidence: 48%
“…4F). Chromosome cytology:-The Asian section Coelocentrum consistently shows the chromosome number of 2n = 30 (Peng et al 2012(Peng et al , 2013(Peng et al , 2014a, with the exception of some probable intraspecific autotriploid individuals with 2n = 45 in B. longgangensis C.- I Peng & Yan Liu (2013: 54-44: 2) (Peng et al 2013). In this study, the diploid count of 2n = 30 was documented for Begonia calciphila (Fig.…”
Section: Introductionsupporting
confidence: 48%
“…To characterize the degree of polymorphism of each locus, 57 individuals from three populations were genotyped using the 60 newly designed primer pairs (Appendix 1). Total genomic DNA was extracted from silica gel-dried leaves based on protocols outlined in Chung et al (2014). The PCR reaction was conducted with a final volume of 20 μL containing approximately 30 ng of genomic DNA, 1 μL of 10 μM of each primer, and 10 μL of 2× Master Mix Red (Ampliqon, Odense, Demark).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The immense terrain of limestone karsts stretching from southern China to northern Vietnam (Sino-Vietnamese limestone karsts; SVLK) is a renowned biodiversity hotspot. It is noted for extremely high species diversity and endemicity of narrowly distributed calciphilous plants that are increasingly threatened by habitat destruction caused by rapid economic growth in recent decades (Chung et al, 2014). To design effective conservation strategies, a better understanding of the evolutionary mechanisms underlying the rich and distinct SVLK flora is essential.…”
Section: Applications In Plant Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…After review of the type specimens and taxonomic publications within the regions (Gagnepain 1921; Irmscher 1939; Ho 1991; Nguyen 2004; Shui and Chen 2005; Truong et al 2005; Nguyen and Tebbit 2006; Kiew 2007; Nguyen et al 2010; Peng et al 2014, 2015a,b; Hughes et al 2015), seven new species of Begonia have been confirmed, and their sectional positions designated here (Doorenbos et al 1998; Shui et al 2002). Due to the taxonomic complexity of the genus (Thomas et al 2011; Chung et al 2014), the DNA samples of the above new species have also been collected and some possible different opinions will be issued about their systematic position in the broad context in the future.…”
Section: Introductionmentioning
confidence: 85%